An endogene‐resembling transgene delays the onset of silencing and limits siRNA accumulation. Issue 6 (1st February 2013) - Dadami, Elena; Moser, Mirko; Zwiebel, Michele; Krczal, Gabi; Wassenegger, Michael; Dalakouras, Athanasios
Abstract : In plants, transgenes are generally more sensitive against RNA silencing than endogenes are. In this study, we generated a transgene that structurally mimicks an endogene. It is composed of endogenous promoter, 5′‐UTR, introns, 3′‐UTR and terminator elements. Our data revealed that, in contrast to a conventional transgene, an endogene‐resembling transgene was more stably expressed and poorly processed into small RNAs. In addition, although both constructs triggered methylation of homologous DNA sequences at similar levels, the endogene‐resembling transgene exhibited significantly delayed onset of local and systemic silencing. Abstract : ► We investigated why transgenes are more prone to silencing than endogenes. ► We produced an endogene‐like transgene (GFP endo ). ► GFP endo was poorly processed to small RNAs. ► GFP endo delayed the onset of systemic silencing. ► Introns and UTRs may be introduced in transgenes to avoid silencing.